크리스토펠 기호

수학노트
http://bomber0.myid.net/ (토론)님의 2010년 4월 11일 (일) 07:14 판
둘러보기로 가기 검색하러 가기
  • 제1기본형식을 이용한 표현
    \(\Gamma^1_{11}=\frac{GE_u-2FF_u+FE_v}{2(EG-F^2)}\)
    \(\Gamma^1_{12}=\frac{GE_v-FG_u}{2(EG-F^2)}\)
    \(\Gamma^1_{22}=\frac{2GF_v-GG_u-FG_v}{2(EG-F^2)}\)
    \(\Gamma^2_{11}=\frac{2EF_u-EE_v-FE_u}{2(EG-F^2)}\)
    \(\Gamma^2_{12}=\frac{EG_u-FE_v}{2(EG-F^2)}\)
    \(\Gamma^2_{22}=\frac{EG_v-2FF_v+FG_u}{2(EG-F^2)}\)
  • \(F=0\) 인 경우
    \(\Gamma^1_{11}=\frac{E_u}{2E}\)
    \(\Gamma^2_{11}=\frac{-E_v}{2G}\)
    \(\Gamma^1_{12}=\frac{E_v}{2E}\)
    \(\Gamma^2_{12}=\frac{G_u}{2G}\)
    \(\Gamma^1_{22}=\frac{-G_u}{2E}\)
    \(\Gamma^2_{22}=\frac{G_v}{2G}\)
  •  
    이 항목의 스프링노트 원문주소
     
     
개요
 
 
재미있는 사실
 

 

 

역 사

 

 

 

메 모

 

 

관련된 항목들

 

 

수학용어번역

 

 

사전 형태의 자료

 

 

관 련논문

 

 

관련도서

 

 

관 련기사

 

 

블 로그
  •